A balanced portfolio can have a higher geometric return than the risky asset - Miriam Arden; Tiemen Woutersen (Journal of Risk and Financial Management, 2021)
In the U.S., the geometric return on stocks has been higher than the geometric return on bonds over long periods. We study whether balanced portfolios have a larger geometric return (and expected log return) than stock portfolios when the risk premium is low. We use a theoretical model and historical data and find that this is the case. This low-risk premium is often observed in other developed countries. Further, in the past two decades, a balanced portfolio with 70% or 90% invested in the U.S. stock market (with the remainder invested in U.S. government bonds) performed better than a 100% stock or bond portfolio. The reason for this is that a pure stock portfolio loses a large fraction of its value in a downturn. We show that this result is not driven by outliers, and that it occurs even when the returns are log normally distributed. This result has broad policy implications for the construction of pension systems and target-date mutual funds.
Keywords: E4; G1; G5; 330; stock return; balanced portfolio; bond return; recession